2019
DOI: 10.2147/dmso.s199802
|View full text |Cite
|
Sign up to set email alerts
|

<p>A small molecule inhibitor MCC950 ameliorates kidney injury in diabetic nephropathy by inhibiting NLRP3 inflammasome activation</p>

Abstract: Background Diabetic nephropathy (DN) is a lethal diabetic microvascular complication characterized by chronic low-grade inflammation. The NOD-like receptor pyrin domain-containing protein 3 (NLRP3) inflammasome is implicated in the progression of DN. MCC950 is a selective and potent inhibitor of NLRP3; however, its efficacy in DN requires further investigation. Methods To investigate the efficacy of MCC950 in DN, eight-week-old type 2 diabetic db/db … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 49 publications
2
68
1
Order By: Relevance
“…18 Chronic sterile inflammation has been proved to be the crucial basis for the progression of DKD. [19][20][21] Our previous study also demonstrated the participation of pyroptosis in diabetic tubular cells. 22 However, whether apoptosis could be an effective treatment target remained controversial hitherto.…”
Section: Discussionmentioning
confidence: 73%
“…18 Chronic sterile inflammation has been proved to be the crucial basis for the progression of DKD. [19][20][21] Our previous study also demonstrated the participation of pyroptosis in diabetic tubular cells. 22 However, whether apoptosis could be an effective treatment target remained controversial hitherto.…”
Section: Discussionmentioning
confidence: 73%
“…At present, the incidence of DN is increasing year by year, which seriously threatens the prognosis and quality of life in diabetic patients [25]. The occurrence and development of DN are related to the disorder of glucose and lipid metabolism, oxidative stress, inflammatory reaction, and abnormal vasoactive substances [26,27]. In this study, the TCM-active ingredient-target network showed that the main active ingredient of AM quercetin, 7-O-methylisomucronulatol, formononetin, and isorhamnetin plays an important role in the network, indicating that they have potential research value in the treatment of DN.…”
Section: Discussionmentioning
confidence: 99%
“…In the diabetic apolipoprotein E knockout (apoE-/-) mice, administration of PPAR-γ agonist pioglitazone downregulated the expression of AGEs, RAGE, and NF-κB, and also diminished NLRP3, caspase-1, IL-18, and IL-1β levels [228]. MCC950, a selective inhibitor of NLRP3 andM920, a broad specificity caspase inhibitor, improved renal function, GBM thickening, podocyte injury, renal fibrosis, and NLRP3-dependent markers in db/db mice [229,230].…”
Section: Nod-like Receptorsmentioning
confidence: 99%